2021
DOI: 10.1038/s41467-021-21022-9
|View full text |Cite
|
Sign up to set email alerts
|

Blood-brain barrier opening with focused ultrasound in Parkinson’s disease dementia

Abstract: MR-guided focused ultrasound (MRgFUS), in combination with intravenous microbubble administration, has been applied for focal temporary BBB opening in patients with neurodegenerative disorders and brain tumors. MRgFUS could become a therapeutic tool for drug delivery of putative neurorestorative therapies. Treatment for Parkinson’s disease with dementia (PDD) is an important unmet need. We initiated a prospective, single-arm, non-randomized, proof-of-concept, safety and feasibility phase I clinical trial (NCT0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(147 citation statements)
references
References 33 publications
3
134
0
Order By: Relevance
“…Pre-clinical studies have demonstrated that low-intensity pulsed ultrasound in combination with systemically injected microbubbles could temporarily open the BBB in a localized manner (244). This concept is currently undergoing clinical trials, and has already demonstrated safety and tolerability in patients, and therefore may provide enhanced systemic OV delivery capabilities (245,246). For intratumoral delivery only, 1) the expense and complexity of neurosurgical procedures, limiting repeat administration.…”
Section: Overcoming Existing Obstacles In Ovs Deliverymentioning
confidence: 99%
“…Pre-clinical studies have demonstrated that low-intensity pulsed ultrasound in combination with systemically injected microbubbles could temporarily open the BBB in a localized manner (244). This concept is currently undergoing clinical trials, and has already demonstrated safety and tolerability in patients, and therefore may provide enhanced systemic OV delivery capabilities (245,246). For intratumoral delivery only, 1) the expense and complexity of neurosurgical procedures, limiting repeat administration.…”
Section: Overcoming Existing Obstacles In Ovs Deliverymentioning
confidence: 99%
“… 25 The importance of this emerging technology is further underscored by successful Phase I clinical trials in Alzheimer’s disease and Parkinson’s disease patients that support the feasibility and safety of BBB opening with low intensity focal sonication. 100 , 101 With ongoing improvements to vector design and CNS delivery, combinatorial gene therapies targeting cell survival and α-syn may offer long-lasting benefits by specifically targeting affected neuronal pathways implicated by prodromal disease symptoms, and which could mitigate further transmission of synucleinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Two sessions of FUS were given with an interval of 2–3 weeks and without side effects. There were mild cognitive improvements, but no major changes in amyloid plaques were detected using 18 F-FDG PET [ 110 , 111 ].…”
Section: Clinical Translation Of Bbbomentioning
confidence: 99%